Scoliosis and the Subsequent Risk of Depression: A Nationwide Population-based Cohort Study in Taiwan. Issue 3 (February 2016) - Chang, Wei-Pin; Lin, Yaleng; Huang, Hsiao-Ling; Lu, Hsing-Fang; Wang, Shih-Tien; Chi, Ying-Chen; Hung, Kuo-Sheng; Chen, Hsiang-Yin
Abstract : Study Design: A retrospective cohort study by using the Taiwanese National Health Insurance Research Database (NHIRD). Objective: The purpose of this study is to conduct a large-scale cohort study to investigate the relationship between scoliosis and depression. Summary of Background Data: The association between scoliosis and depression has rarely been studied in Asian populations. Methods: The study cohort consisted of patients with diagnosis of scoliosis between 2003 and 2005 (N = 1409). A comparison cohort was constructed from five age- and gender-matched control subjects selected via random sampling (N = 7045). Data on adjusted hazard ratios (AHRs) of depression, 5-year freedom from depression rates, and risk factors for depression for the two cohorts were compared. All subjects were tracked for 5 years from the date of cohort entry to identify the development of depression. Cox proportional hazard regressions were performed to evaluate the 5-year freedom from depression rates. This study is supported by the University research grant without any study-specific conflicts. Results: During the 5-year follow-up period, 116 and 307 depression patients belonged to the scoliosis cohort and the comparison cohort, respectively. The AHRs of depression in patients with scoliosis was higher [AHR 1.95; 95% confidence interval (95% CI) 1.58–2.42; P < 0 .001] than that of the controls during the 5-year follow-up. The risk of depression also demonstrated to be age-dependent for scoliosis patients. The middle-age (41–65 years old) and young adults (18–40 years old) scoliosis patients had higher AHRs (middle-age: AHR 2.45; 95% CI 1.67–3.59; P < 0 .05; young adult: AHR 1.99; 95% CI 1.41–2.82; P < 0 .05). Conclusion: The population-based study indicated that patients with scoliosis may have an increased risk of depression. Health care professionals should consider designing and planning effective psychological prevention and treatment for scoliosis patients. Level of Evidence: 4